Erratum: Seepage from an arctic shallow marine gas hydrate reservoir is insensitive to momentary ocean warming - Hong, Wei-Li; Torres, Marta E; Carroll, JoLynn; Crémière, Antoine; Panieri, Giuliana; Yao, Haoyi; Serov, Pavel (Nature Communications, 2017)
Nature Communications 8: Article number:15745 (2017) Published: 7 June 2017; Updated: 30 June 2017 The financial support for this Article was not fully acknowledged. The Acknowledgements should have included the following: The publication charges for this article have been funded by a grant from thepublication fund of UiT The Arctic University of Norway.